Platelet-rich fibrin and calcium hydroxyapatite (CaHA): the perfect combination to accelerate, potentiate, and extend skin rejuvenation - Hernández, Julián; Ruiz Polania, Natalia; Martinez Amado, Andreina; Campuzano, Sebastian (Aesthetic Medicine, 2024)
Background: calcium hydroxyapatite (CaHA), classified as a collagen biostimulator, known commercially as Radiesse® (Merz Pharma GmbH & Co. KGaA, Frankfurt, Germany) contains 30% synthetic CaHA suspended in a 70% aqueous sodium carboxymethylcellulose gel matrix. It provides both volume replacement and collagen biostimulation as a primary mechanism of action and has become one of the most effective treatments to rejuvenate the face. However, after the treatment it is necessary to wait for approximately 4 to 6 weeks to achieve any results. Methods: we included 100 patients, all adults and divided into two groups: 50 patients treated with CaHA filler (Radiesse, Merz North America, Inc., Raleigh, NC) in a "traditional dilution" with 0, 5 ml of 2% lidocaine and 2 ml of standard saline solution, so we have 4 ml in total to use 2 ml per side, and 50 patients treated with our new technique with 1.5 ml of CaHA filler diluted with 2.5 ml of Platelet-rich fibrin (PRF) for a total of 4 ml. Results: Platelet-rich fibrin used as a diluent for Radiesse in facial bio stimulation treatments produces superior results in a shorter timeframe, as demonstrated in this case series. Patients experience a unique radiance in their skin during treatment and can expect a safe profile with no severe complications. Conclusion: Using platelet-rich fibrin and Radiesse together is a simple and effective way to boost the product’s bio-stimulatory effect. This combination could become a key element in anti-ageing medicine to promote cell regeneration.